Exploring the influence of physical activity on lymphedema development in female breast cancer survivors - Duarte, Alice Ralheta (2023)
In recent years, there has been a notable rise in the number of breast cancer survivors, highlighting the advancements in treatment and care. However, the presence of cancer treatment side effects, such as lymphedema (LE), significantly affects the function, active participation, and overall quality of life of these individuals. It is imperative, therefore, to gain a deeper understanding of the most effective strategies for preventing and treating LE. Preventing LE involves promoting active and healthy lifestyles by instilling behavioral changes and addressing modifiable risk factors. Therefore, this study aimed to characterize Portuguese breast cancer survivors' physical activity (PA) levels. A cross-sectional analytical study was conducted. Women who survived breast cancer between 1 and 5 years after surgery were selected. A characterization questionnaire was performed, upper limb lymphedema volume was measured with tape measures and PA levels were assessed with the International Physical Activity Questionnaire (IPAQ-SF). A group of 20 women with a mean age of 61±8 years and an average of 39 months after breast surgery participated in the study. Of those, 80% were overweight, of which 35% were obese. There was an average volume of 2100cm3 in the affected upper limb and an average of 2013cm3 in the unaffected side. The difference between the two limbs presented an average of 87.3 cm3. So far, none of the participants showed a significant difference between limbs (greater than 10% difference). Despite this, 45% of participants have subclinical LE (difference between both upper limbs of 5 to 10%). No significant associations were found between the LE and PA (rs=0.231; p=0.3) nor between LE and the number of hours sitting (rs=0.291, p=0.213). However, a strong positive correlation was found between Body Mass Index (BMI) and limb volume difference (rs=0.583; p=0.007). The study does not provide evidence of a direct association between physical activity (PA) and lymphedema (LE). However, there is a correlation between body mass index (BMI) and lymphedema, and higher BMI is identified as a risk factor for the development of lymphedema. Moreover, engaging in physical activity can contribute to the control and management of BMI, revealing the influence of PA on BMI. Consequently, PA indirectly serves as a preventive strategy against lymphedema by helping to control BMI. By incorporating PA as part of a comprehensive approach to managing BMI, the risk of developing lymphedema may be reduced. In summary, the observations suggest that while PA may not directly prevent lymphedema, it can play an important role in indirectly preventing its development by helping to control BMI.